Gênero e sexualidade : práticas discursivas no cotidiano escolar - Freitas, Maria Jose Dias De [UNIFESP] (2017)
The objective of the study was to know the discursive practices on gender and sexuality among elementary school II and high school students, aiming at pointing out guidelines and contributing to gender equitable public policies. The methodological approach adopted was the qualitative, type of research that has so much importance for the study of the populations to which their way of life, their feelings, beliefs,perceptions and opinions refer. This study hadas its proposal the theoretical-methodological approach to the production of everyday meaningsadvocated by Spink and Frezza (2004), a way of working with language, based onsocial psychology, from a constructionist perspective. In presenting the discursive strand,it was aimed to seek the production of meanings from the everyday discourses and the meanings that are attributed to being a man and being a woman. The study was conducted in two stages, the first of which was attended by 211 students of both genders, between 13and 18 years old. In the second stage, seven students, of both genders, participated in the 15 to 17-year-old group. The inclusion criteria were to be enrolled and attending the last year ofthe elementary school classes II and attending high school. Data collection consisted of applying two research instruments. The first stage applied two open questions to 211 students, and in the second stage, the technique was the focus group (GF) based on the assumptions of discursive strands. The data that emerged from the first step were organized into an Excel spreadsheet, later organizedby Alceste software, which was the first statistical classification of "corpus units" of the studied corpus from the distribution of words in "units", in order to identify the most characteristic words that subsidized the next stage of the study. In the second stage, the most characteristic wordsof the first stage subsided the focus group, which were recorded and transcribed integrally. Next, the thematic analysis was carried out combined on idea association maps, which is a way of decomposing the text to the maximum to reach the essence of the discussion. The empirical material resulting from the focus groups was discussed considering the assumptions of social constructionism. The justification of the choice lies in the accuracy that this theoretical alternative offers, since it makes possible the explanation of the steps of analysis and interpretation in order to foster dialogue. In order to perform the data analysis, Fairclough's Critical Discourse Analysis (ACD) (2012) was adopted, which presents a theoretical perspective on the language andon semiosis. Semiosis includes different forms of production of senses-images, body language and the language itself. This process of signification and meaning production takes place from the analytical structure of the ACD, which has schematic itemsthat combine relational elements with dialogical elements, identify the problematic and how it is its insertion in daily life, its obstacles and how to overcome the discursively presented challenges of being a man and being a woman. The results showed the behavior of adolescents regarding the consideration of the aspects about the discursive practices of gender and sexuality result from the way in which the gender policies in society are configured and their harmfulness for both genres. Sexuality refers to configurations such as bisexuality and open relationships, as well as unprotectedsexual intercourse, which is a situation that increases the conditions of female subjection and subordination. Discursive practices of gender and sexuality are noted on the sexual division of work and sports. During the study, we identified a considerablenumber of cases of disrespect to human rights. Because of that, we recommend that the government acts against sexual and gender violence. It is urgent to take action to increase gender equity and reduce violence against women. Besides, it is important to invest in projects to protect young people, trough education, health and equity.